Development will (try to) find its way: a qualitative study of Chilean adolescent mental health during and after lockdown - Camila Espinoza; Florencia Canessa; Shelley van der Veek; Lenneke Alink; Anja van der Voort (BMC, 2024)
Abstract Background The COVID-19 pandemic has had a well-evidenced impact on adolescents, who are especially sensitive to pandemic disruptions given the critical role of socialization in their development. In Chile too, evidence shows increases in mental health complaints among adolescents over the lockdown period. Our study aimed at exploring the experiences of Chilean adolescents regarding their mental health during the lockdown and school closure (March 2020-December 2021), and during the return to on-site education (2022) as informed by adolescents and school staff, with a focus on family, school, and social sources of risk and support for adolescents' wellbeing during these periods. Methods Using a qualitative approach, we conducted semi-structured interviews with 19 adolescents and 16 staff members from schools in an urban area of Chile. Results Through thematic analysis, we generated five themes: [1] Adolescents in a mental health crisis, comprising a range of distressing experiences and mental health problems. This crisis was fueled by alterations in the functioning of adolescents' systems: [2] Broken support systems (peers and school); [3] The school agenda must go on, reflecting schools' strict compliance with the educational curriculum; and [4] Blurred boundaries between home and school life and within the family. Finally [5], Development will (try to) find its way describes how most participants experienced a bouncing back to wellbeing in the course of the school year upon return, and how some developmental milestones took place despite the abnormal conditions, providing evidence for resilience amid pandemic adversity. Conclusions The findings give insight into how the exchanges between the adolescent and the social systems they are embedded in were interfered. The results help us understand the challenges for mental health during and after the pandemic, and highlight adolescents' capacity to thrive as normality was restored. The results also underscore the importance of upholding stability across adolescents' systems and routines, in order to mitigate impacts on wellbeing amid abnormal circumstances. The findings are relevant for development-informed initiatives in policy design in the aftermath of the pandemic and in future crisis management responses.